Mechanism of penetrating injury mediates the risk of long-term adverse outcomes for survivors of violent trauma. Issue 3 (March 2022) - Pino, Elizabeth C.; Fontin, Francesca; James, Thea L.; Dugan, Elizabeth
Abstract : BACKGROUND: While hospital-based violence intervention programs are primarily designed to aid youth victims of gun violence at high risk for reinjury, the root causes and complex outcomes of community violence are varied. In this study, we examined the risk factors for violent penetrating injury and how the risk of adverse outcomes for survivors differs by injury type (stabbing vs. gunshot wound). METHODS: This retrospective study was performed using a cohort of patients presenting to the Boston Medical Center emergency department for a penetrating injury due to community violence between 2006 and 2016. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) for the risk of all-cause mortality and violent reinjury within 3 years after surviving a penetrating injury. RESULTS: Of the 4, 280 survivors of the initial violent penetrating injury, there were 88 deaths (2.1%) and 568 violent reinjuries (13.3%) within 3 years. Compared with gunshot wound victims, stab wound victims were 31% less likely to be reinjured with a gunshot wound (HR, 0.69; 95% CI, 0.51–0.93), 72% more likely to be reinjured with a stab wound (HR, 1.72; 95% CI, 1.21–2.43), and 49% more likely to be reinjured by assault (HR, 1.49; 95% CI, 1.14–1.94). While survivors of stabbing and firearm injuries were equally at risk for 3-year all-cause mortality, stab wound victims were 3.75 times more likely to die by a drug/alcohol overdose (HR, 3.75; 95% CI, 1.11–20.65). CONCLUSION: Patients surviving a stab wound have a significantly higher risk of violent reinjury by stabbing or assault, and risk of death by drug/alcohol overdose. Hospital-based violence intervention programs with similar patient populations should explore options to expand partnerships with drug treatment programs. These results illustrate two distinct populations of victims of violence─gunshot victims and stabbing/assault victims─with separate risk factors and outcomes, mediated by substance use disorder. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; level III. Abstract : Supplemental digital content is available in the text.